(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This research was conducted to study the factors affecting the use of Information and Communication Technologies (ICTs) by Southern Colleges Teachers in Balqa applied university teachers. The results of this study indicate that even though a majority of respondents use ICT in teaching activities. The descriptive results indicated that teachers had high level of knowledge and skill in applying ICT. In addition, computer and internet are available to majority of respondents. It appeared from the findings of this research that technologies are used at the high level. Providing more availability of ICT to teachers as the most producers of the information and knowledge will be essential. The findings of regression analysis also showed that the skill in using ICT explained 3.63 of extent to which faculty members used ICT variance. This result refers to the fact that holding educational courses aiming at increasing people’s familiarity and knowledge about ICT will improve the usage of these technologies.